Cr diffusion and continuous repairing behavior during high‐temperature oxidation of duplex stainless steel. Issue 10 (24th April 2017) - An, L.C.; Cao, J.; Zhang, T.; Yang, Y.T.
Abstract : The initial oxidation behavior of duplex stainless steel was investigated at different temperatures in laboratory conditions through scanning electronic microscopy and Raman spectroscopy. Continuous repairing behavior was observed as the increased diffused Cr content induced increased ferrite phase transformation. The ferrite diffusion layer became thicker with increasing oxidation temperature. Abstract : The initial oxidation behavior of duplex stainless steel was investigated at different temperatures in laboratory conditions through scanning electronic microscopy and Raman spectroscopy. Increased diffused Cr content could induce increased ferrite phase transformation into austenite and a denser Cr2 O3 layer, which could lead to the continuous repairing effect of the ferrite diffusion layer.